Excluded by crisis management? Legislative hyperactivity in post-2015 Germany - Constantin Hruschka; Tim Rohmann (International Migration, 2021)
This article examines the legislative measures taken by Germany since 2014 to manage the “refugee crisis” and analyses the potential effects on the rights and the well-being of asylum seekers and persons with protection needs at large. By taking a closer look at the reasoning given in the respective legislative documents we will show the link between the recent changes in the national asylum and migration law and the underlying migration management framework. The article concludes that Germany has seen a shift from a management to a securitization approach, the latter entailing a special emphasis on deportation (“return turn”) rather than focusing on accommodation and integration of those seeking protection. Acting in a mere “crisis mode”, the German legislator has implemented an exclusion paradigm that incrementally substituted the prior inclusive policies over time.
Keywords: 300